Penggunaan Antipsikotik pada Lansia dan Efek Kardiovaskular: Evidence Based Case Report - Kasmianto Abadi; Natalia Widiasih; Profitasari Kusumaningrum; Martina W.Nasrun (Majalah Kedokteran Indonesia, 2018)
Background: Effects of antipsychotics in the elderly (elderly) is associated with cardiovascular side effects. Some cardiovascular side effects can occur in the elderly and can cause sudden death. The type of antipsychotics used is thought to be related to the incidence of cardiovascular mortality.Methods: A structured search was conducted at Pubmed, EBSCO, and Science Direct using keywords based on the Boolean operators concept that was suitable for clinical questions. The target population is elderly patients who use antipsychotics and effects on the cardiovascular system.Results: After filtering 68 titles and abstracts using inclusion and exclusion criteria, 2 articles were obtained. Furthermore, a critical review is based on validity, importance of results, and application. Both articles showed a significant association between the use of antipsychotics and the incidence of cardiovascular mortalityConclusions: The use of antipsychotics in the elderly can lead to cardiovascular mortality risk, it is necessary to assess the profile of the benefits and risks of using antipsychotic drugs as well as dose adjustments and evaluation of side effects.